Individual and facility-level factors associated with women's receipt of immediate postpartum family planning counseling in Ethiopia: results from national surveys of women and health facilities - Alexandria K. Mickler; Celia Karp; Saifuddin Ahmed; Mahari Yihdego; Assefa Seme; Solomon Shiferaw; Linnea Zimmerman (BMC, 2021)
Abstract Background Immediate postpartum family planning (IPPFP) helps prevent unintended and closely spaced pregnancies. Despite Ethiopia's rising facility-based delivery rate and supportive IPPFP policies, the prevalence of postpartum contraceptive use remains low, with little known about disparities in access to IPPFP counseling. We sought to understand if women's receipt of IPPFP counseling varied by individual and facility characteristics. Methods We used weighted linked household and facility data from the national Performance Monitoring for Action Ethiopia (PMA-Ethiopia) study. Altogether, 936 women 5-9 weeks postpartum who delivered at a government facility were matched to the nearest facility offering labor and delivery care, corresponding to the facility type in which each woman reported delivering (n = 224 facilities). We explored women's receipt of IPPFP counseling and individual and facility-level characteristics utilizing descriptive statistics. The relationship between women's receipt of IPPFP counseling and individual and facility factors were assessed through multivariate, multilevel models. Results Approximately one-quarter of postpartum women received IPPFP counseling (27%) and most women delivered government health centers (59%). Nearly all facilities provided IPPFP services (94%); most had short- and long-acting methods available (71 and 87%, respectively) and no recent stockouts (60%). Multivariate analyses revealed significant disparities in IPPFP counseling with lower odds of counseling among primiparous women, those who delivered vaginally, and women who did not receive delivery care from a doctor or health officer (all p < 0.05). Having never used contraception was marginally associated with lower odds of receiving IPPFP counseling (p < 0.10). IPPFP counseling did not differ by age, residence, method availability, or facility type, after adjusting for other individual and facility factors. Conclusion Despite relatively widespread availability of IPPFP services in Ethiopia, receipt of IPPFP counseling remains low. Our results highlight important gaps in IPPFP care, particularly among first-time mothers, women who have never used contraception, women who delivered vaginally, and those who did not receive delivery care from a doctor or health officer. As facility births continue to rise in Ethiopia, health systems and providers must ensure that equitable, high-quality IPPFP services are offered to all women.